Fluid reasoning and the developing brain - Ferrer, Emilio; O'Hare, Elizabeth D.; Bunge, Silvia A. (Frontiers in Neuroscience, 2009)
Fluid reasoning is a cornerstone of human cognition, both during development and in adulthood. In spite of this, the neural mechanisms underlying the development of fluid reasoning are largely unknown. Here we provide an overview of this important cognitive ability, how it is measured, how it changes over childhood and adolescence, and what is known about its neurobiological underpinnings. We review important findings from the psychometric, cognitive, and neuroscientific literatures, and outline important future directions for this interdisciplinary research.